An empirical analysis of risk, incentives and the delegation of worker authority - Jed Devaro; Fidan Ana Kurtulus (University of Massachusetts, Department of Economics, 2011)
We address four empirical questions in this paper. Is there empirical support for: 1) the risk-incentives tradeoff predicted by agency theory? 2) a positive relationship between authority and incentives? 3) a positive relationship between risk and authority? 4) the main testable implication of Prendergasts model, namely that the risk coefficient in an incentives regression should become smaller (i.e. less positive or more negative) when delegation of worker authority is incorporated into the riskincentives regression model? Our empirical results support affirmative answers to all four questions, though in some cases the relevant parameters are estimated with low precision. Thus, our analysis contributes to the literature by providing empirical evidence clarifying the relationship between risk and incentive pay and how managers optimally bundle incentive pay and the delegation of worker decision rights to cope with risk. In particular, we attempt to reconcile the mixed nature of the empirical literature concerning evidence for a riskincentives tradeoff by empirically addressing Prendergasts extension of the standard principal-agent model.
Keywords: D21; D23; D81; M51; M52; M54; 330; Agency Theory; Risk versus Incentives Tradeoff; Delegation of Worker Authority; Performance Pay